PANDANGAN SISWA TERHADAP DESAIN BERBANTUAN KOMPUTER DALAM PELATIHAN SOLIDWORKS DI SMK NUSANTARA KUDUS - Andreas Prasetyadi; I Made Wicaksana; Budi Setyahandana; I Gusti Ketut Puja; Stefan Mardikus; Raden Benediktus Dwiseno Wihadi; Heryoga Winarbawa; Rines Rines (Universitas Sanata Dharma, 2022)
An activity of collaboration between Mechanical Engineering Department of Sanata Dharma University and SMK Nusantara Kudus was conducted. The percepetion of High School Students of SMK Nusantara Kudus about Computer Aided Design was measured during the Solidworks Training as the main activity. Pre- and Post-Questionnaires were delivered among the 20 students joining the activity. Nineteen of them returned the questionnaires of 10 positive statements with 3 conditions of answers i.e. agree, disagree, and undecided. The results show that the students mostly are interested in designing manually and computer based. It also mentions that they appreciate CAD skills as their important future work skill. The activity did not affect the interest of the students in term of designing but helped them to be more engaged to the CAD.